Elements of the pedagogical design of MOOC «Statistics for researchers» - Purificación GALINDO VILLARDÓN; M.ª Purificación VICENTE GALINDO (Ediciones Universidad de Salamanca, 2018)
We present the constituent elements of the pedagogical design of MOOC «Statistics to researchers» from the University of Salamanca to the goal of detailing its pedagogical design and the results obtained. We start from four themes: (I) type of statistical learning, features and the propositional network for its representation; (II) capabilities of the virtual environment to enhance the transfer of knowledge; (III) materials as resources to learning; (IV) the analysis of the technological tools. A case study-based research methodology is adopted and used the questionnaire as an instrument. We present the results of implementation proving its success with a 30% completion rate.